CONTROLLING FACTORS OF MARKETING ACTIVITIES: A CASE STUDY OF FRUIT PROCESSING INDUSTRIES IN EAST JAVA, INDONESIA - I B Suryaningrat (UNEJ e-Proceeding, 2012)
In East Java, Fruit Processing Industries (FPIs), are a key part of agroindustrial activities there. In term of agroindustry, three basic components in any agroindustrialsystem are procurement of raw material, processing and marketing. How to encourage fruit processing, as an agroindustrial activity and area potential, has become a crucial issue and a major priority for area development in East Java. Understanding the problems in FPIswould give support to success cases. Based on a sample survey of five districts in East Java province (Banyuwangi, Jember, Lumajang, Probolinggo and Malang), this paper reviews controlling factors, especially marketing activities, based on three basic components of the agroindustrial system. The paper concludes that in term of SMFPIs, education and technology are considered as determinant factors of marketing activities. The existence of big industries has strong effect to marketing performance. Understanding these factors can aid policy makers of FPIs in designing and implementing appropriate programs.